Preliminary Study on the Clinical and Genetic Characteristics of Hereditary Spherocytosis in 15 Chinese Children - Wu, Chongjun; Xiong, Ting; Xu, Zhongjin; Zhan, Chunlei; Chen, Feng; Ye, Yao; Wang, Hong; Yang, Yu (Frontiers in Genetics, 2021)
Objective To investigate the clinical and genetic characteristics of hereditary spherocythemia (HS) in Chinese children, and to analyze the potential genotypic/phenotypic associations. Methods The clinical data and gene test results of children with HS were collected. All patients were diagnosed by gene test results, and the laboratory results were obtained before splenectomy. The data of red blood cell (RBC), hemoglobin (HB), mean red blood cell volume (MCV), mean red blood cell hemoglobin (MCH), mean red blood cell hemoglobin concentration (MCHC), and hematocrit (HCT) were statistically analyzed according to different mutation genes. Statistical methods for comparison between groups Mann–Whitney test analysis, two-terminal p < 0.05 was considered significant difference. Results A total of 15 children were enrolled in our hospital, and 14 variants were found (nine variants have not been reported before), including 10 ANK1 mutations (seven ANK1 truncated mutations) and five SPTB mutations. Patients with ANK1 mutations had more severe anemia than those with SPTB mutations (significantly lower RBC, HB, MCHC, and HCT). Conclusion This is one of the few studies on the genetic and clinical characteristics of children with HS in China. This study identified the unique genetic and clinical characteristics of Chinese children with HS and analyzed the pathogenic genotype–phenotypic association. The results confirmed that the anemia degree of HS patients caused by ANK1 was more serious than that of patients with SPTB deficiency. However, further study of the correlation between genotype and phenotype requires a larger sample size.